Hedonic capital - Liam Graham; Andrew J. Oswald (Institute for the Study of Labor (IZA), 2006)
This paper proposes a new way to think about happiness. It distinguishes between stocks and flows. Central to the analysis is a concept we call 'hedonic capital'. The paper sets out a model of the dynamics of wellbeing in which bad life-shocks are smoothed by the drawing down of hedonic capital. The model fits the patterns found in the empirical literature: the existence of a stable level of wellbeing and a tendency to return gradually towards that level. It offers a theory of hedonic adaptation.
Keywords: D1; I3; 330; adaptation; wellbeing; evolution; happiness; habituation